EVALUATION OF WATER DEFICIT IN ARROIO DOS RATOS SOIL, ELDORADO DO SUL, RS - JOBIM, CARMEM ILSE PINHEIRO (1999)
In the State of Rio Grande do Sul, the losses of spring-summer crops by drought events has showed the necessity of specific studies about local water deficit regarding the irrigation practice. Depressão Central lowlands, specifically the Arroio dos Ratos soil, are usefitl alternative to wet rice and are suitable for irrigation. So, the water deficit occurrence in the spring-summer period in Eldorado do Sul, with Arroio dos Ratos soil, were studied, adopting a soil water-storage capacity of 67.71 mm. The homogeneous serial dates of the 1967-1993 period were used to evaluate the referential evapotranspiration, and to compute the average water balance and the serial water balance for ten-day periods. The deficit and water indexes frequency were calculated. The results showed that water deficit occurs from November through March, however December, January and February were the months with the most frequent and severe water deficit.